2018
DOI: 10.18805/ijar.b-971
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between body condition score and hormone level of Bali cattle with postpartum anestrus

Abstract: Body Condition Score (BCS) is a simpler and more practical method to evaluate the body’s energy and fat reserves in cows. Nutrition play a direct role both in the hypothalamus by synthesizing and releasing GnRH, as well as on the anterior pituitary by controlling the synthesis and release of Leptin, FSH, LH and Estrogen. The purpose of this study was to determine the relationship between the body condition score with the activation of hormones in the hypothalamic–pituitary–gonadal axis on Bali cattle that expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Luteinizing hormone plays a substantial role in contributing ovarian inactivity in buffaloes (Razdan et al 1981).In this study, the average concentrations of serum LH hormone samples were recorded in the 1 st group (ovarian inactivity) (1.98 ± 0.088), 2 nd group (silent heat) (2.17 ± 0.057) and 3 rd group (control) (2.2 ± 0.068). These results were in contact with Agustina (2019) and Taher et al (2020) who reported the reduction in both FSH and LH in inactive ovaries. Other related studies Janakiraman et al (1980); Aboul-Ela and Barkawi (1988); Singh and Chaudhry (1992) recorded that secretion was lower during summer compared to winter.…”
Section: Discussionsupporting
confidence: 85%
“…Luteinizing hormone plays a substantial role in contributing ovarian inactivity in buffaloes (Razdan et al 1981).In this study, the average concentrations of serum LH hormone samples were recorded in the 1 st group (ovarian inactivity) (1.98 ± 0.088), 2 nd group (silent heat) (2.17 ± 0.057) and 3 rd group (control) (2.2 ± 0.068). These results were in contact with Agustina (2019) and Taher et al (2020) who reported the reduction in both FSH and LH in inactive ovaries. Other related studies Janakiraman et al (1980); Aboul-Ela and Barkawi (1988); Singh and Chaudhry (1992) recorded that secretion was lower during summer compared to winter.…”
Section: Discussionsupporting
confidence: 85%
“…Puberty in animals does not indicate a standard and perfect reproductive capacity. The appearance of puberty is marked by changes in the external genitalia during estrus, such as redness of the vaginal mucosa, discharge from the vagina, and swelling of the vulva (Laksmi et al, 2019). In the form of concentrate, supplementary feedings such as calcium, phosphorus, crude protein, fat, and fiber show a faster estrus emergence time than others without the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This explains why a close relationship exists between body condition score and reproductive hormone level in Bali cattle with postpartum anestrus. BCS 3 tends to produce more estrus in a minimal amount of time, while BCS 2 cattle can experience delays in the emergence due to ovarian hypofunction (Laksmi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It takes longer compared to the results of previous studies ranging from 28-43 days. It was stated (Laksmi et al, 2019) that the average time of first and second ovulation of primiparous cattle is 27.67 and 47.67 days postpartum, while the average time of first and second ovulation of pluriparous cattle is 28.33 and 43.33 days postpartum. This showed a correlation between body condition scores and hormone levels, namely Leptin levels of 0.861; LH level of 0.960; FSH level of 0.799; and Estrogen level of 0.761 (Laksmi et al, 2019).…”
Section: Post-partum Estrus Of Female Balinese Cattle In East Halmahe...mentioning
confidence: 99%